Proinflammatory Cytokines and Its Correlation with Liver Injury - Tri Nugraha Susilawati; Winda Rahayuningtyas; Triyanta Yuli Pramana (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: A persistent infection of hepatitis B virus (HBV) can cause liver cirrhosis and hepatocarcinoma even though the virus itself is non-cytopathic and does not cause cell injury. It has been asserted that liver injury in chronic HBV infection is attributed to the host immune system responding to HBV infection. Cytokines have a critical role in mediating immune responses to viral infection. This study aimed to determine the correlation between the levels of serum IFN-γ, IL-2, IL-17, and TNF- α with the progress of chronic HBV infection that was determined through provisional diagnosis, patient’s age, and the levels of serum transaminases.Method: Blood samples were collected from patients with chronic hepatitis B and the levels of serum IFN-γ, IL-2, IL-17, and TNF-α were measured by using ELISA. The correlation between each cytokine levels and the provisional diagnosis, patient’s age, and serum transaminases were analyzed by using the Spearman correlation test with a p value of 0.05 is considered as statistically significant.Results: A total of 47 samples were collected from patients with chronic hepatitis B (n=38), chronic hepatitis B with liver cirrhosis (n = 6), and chronic hepatitis B with hepatocellular carcinoma (nc = 3). A significant correlation was found between the levels of serum IFN-γ and aspartate aminotransferase (AST) (p = 0.04).Conclusion: The increase of serum IFN-γ and AST levels may highlight the importance of these particular cytokine and liver transaminase in the immune response to chronic HBV infection since IFN-γ is capable to induce apoptotic cell death which promotes AST release and facilitates liver injury.